French animation history - Neupert, Richard John. (Oxford ; Malden : Wiley-Blackwell, 2011)
Animation: History and Narration is the first text book designed to introduce readers to a wide range of significant cartoons, chronicle animation's rich history, and establish productive critical approaches for rethinking the fascinating variety of animated storytelling. This comprehensive volume charts the evolution of the cartoon from from its simplistic--even crude--birth at the turn of the 20th Century to the dazzling high-tech manipulations of Dreamworks' and Pixar Studios and the popularity of the Cartoon Network. The overall structure of Animation: History and Narration.
Introduction: the rise of animation in France -- Silent animation: Emile Cohl and his artisanal legacy -- French animation and the coming of sound -- Toward an alternative studio structure -- French animation's renaissance -- Conclusion: French animation today.
Includes bibliographical references and index.
Print version record.
Keywords: Animated films -- France -- History and criticism; Animated films -- France -- History and criticism; PERFORMING ARTS -- Animation; Animated films; France; Electronic books; Criticism, interpretation, etc